Tumor budding as a prognostic criterion of colorectal cancer - I. I. Yakovtsova; V. M. Cheverda; O. V. Dolhaia; A. S. Yakymenko; I. V. Ivakhno (Zaporozhye State Medical University, 2021)
Colorectal cancer (CRC) is the second leading cause of mortality among cancers after malignant tumors of respiratory system. One of the most significant prognostic features of CRC is tumor budding (TB), which isn't widely implemented in clinical practice. The aim of this research: to find the prognostic criteria of recurrence and lethal outcome of CRR IIA and IIIB stages (рТ3N0-2M0), the ratio of tumors with certain differentiation in groups of research was taken equal. Material and methods. The group I was formed from primary CRC without recurrences. The main relapse-free survival time was 5 years (62.5 ± 16.5 months). The ІІ group - primary CRC with recurrences; ІІА - with recurrences during 5 years from the moment when the tumor was removed, without fatal outcome; ІІВ - with recurrences and lethal outcome from generalization of tumor process during 5 years from the moment when the tumor was removed. The microslides of CRC were made by using the standard methods. Results. TB was identified in 46.66 % (28/60) of CRC рТ3N0-2M0. The direct relationship between tumor grade and presence of TB was found (Р < 0.05), but TB didn't define differentiation of the CRC. There was a statistically significant relationship between TB and metastatic spreading of CRC to regional lymph nodes (Р < 0.001). Metastasis was associated with 3 stage of TB, absence of metastasis was typical for CRC without TB. The tendency was found in a larger number of cases of the CRC with TB 3 stage among recurring CRC compared with CRC without recurrence, mainly due to the ІІВ group of the research. Inverse correlation between TB stage and time of recurrence appearance was found (Р < 0.05). TB in central tumor sites was followed by presence and higher stage of TB in peripheral tumor sites (Р < 0.05), that can be taken into account during biopsies of CRC. Conclusions. TB is a prognostic criterion of metastasis and time of recurrence appearance for CRC рТ3N0-2M0, which is mostly typical for tumors in patients with recurrences and lethal outcome at the taken equal ratio of tumors by differentiation.